2013
DOI: 10.9734/ajea/2013/3902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pre-Emergence Herbicides for Weed Control in Cowpea (Vigna unguiculata (L.) Walp.) in a Forest - Savanna Transition Zone

Abstract: Aims: To evaluate the efficacy and economic benefits of selected pre-emergence herbicides for weed control in cowpea. Study Design: Randomized complete block design with four replications was used. Place and Duration of Study: Research and Teaching Farm of Ambrose Alli University in Ekpoma (Lat. 6 º 45'N, Long. 6 º 8'E), in a forest-savanna transition zone of Nigeria, between August and December 2005 and August and December 2006. Methodology: Five weed control treatments evaluated against unweeded control were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
3
4
1
Order By: Relevance
“…is result is in line with the finding of Sunday and Ekea [31] who identified that the synergic influences of fertilizers in stimulation of cell division enhancement, cell growth promotion, and vegetative growth were prolonged for reasonably longer period owing to ample supplies of macronutrients and possibly other micronutrients in rice.…”
Section: Phenology and Growthsupporting
confidence: 91%
See 1 more Smart Citation
“…is result is in line with the finding of Sunday and Ekea [31] who identified that the synergic influences of fertilizers in stimulation of cell division enhancement, cell growth promotion, and vegetative growth were prolonged for reasonably longer period owing to ample supplies of macronutrients and possibly other micronutrients in rice.…”
Section: Phenology and Growthsupporting
confidence: 91%
“…is delayed maturity of a crop might be due to that effective control of the weeds by these treatments and also fewer struggle for moisture, quantum of light, and ion of nutrients and more free space owing to better utilization of resources as a consequence of less weed antagonism so that crops stay more in vegetative growth which ultimately resulted into significant increase of 90% physiological maturity. e result was in contradiction with the analysis of Sunday and Ekea [31] who quantified that giving plots with herbicides and complementing with hand weeding at intervals helped to reduce the number of days to maturity. On the other hand, statistical analysis of the data indicated that the earliest time to reach physiological maturity (101 days) of a crop was found at weedy plots.…”
Section: Phenology and Growthcontrasting
confidence: 70%
“…Also, the low weed density observed in herbicides treated plots could be attributed to effective weed control of the herbicides and their ability to manage weeds beyond the critical period of cowpea growth. Also, the adequate weed cover by cowpea vine led to smothering effect of the weeds judging from the low weed population and low weed dry weight, which invariably led to increase in weed smothering efficiency [22]. They also found lower weed dry matter and higher weed control efficiency with herbicides+hand weeding than other treatments included in their experiment.…”
Section: Weed Parametersmentioning
confidence: 88%
“…Sunday and Udensi, (2013) reported that control weed growth and/or inadequate weed control in the crop have been reported to account for 40-80% reduction in grain yield in cowpea.…”
Section: Yield Losses Due To Weedsmentioning
confidence: 99%